Hyperuricemia in diabetic kidney disease patients presenting to a tertiary care hospital of Khyber Pakhtunkhwa: a cross sectional Study - Ayaz, Muhammad; Ullah, Hayat; Rehman, Ayesha; Khan, Muhammad Imad; Haq, Fazle; Uddin, Iftikhar (International Journal of Pathology, 2025)
Background: Hyperuricemia is commonly observed in patients with diabetic kidney disease (DKD) and is believed to contribute to worsening renal outcomes. Limited local data exist to highlight the burden of hyperuricemia in these patients in Pakistan. We want to determine the prevalence of hyperuricemia in patients with DKD presenting to a tertiary care hospital in Khyber Pakhtunkhwa. Methods: This Descriptive cross-sectional study was conducted at the Nephrology unit of Lady Reading Hospital, Peshawar, from May to October 2024. A total of 237 patients having T2DM and chronic kidney disease were enrolled using non-probability consecutive sampling. DKD was defined as an estimated glomerular filtration rate (eGFR) <60 mL/min/1.73 m^2 and/or albuminuria >30 mg/g for more than 3 months. Hyperuricemia was characterized by serum uric acid concentrations above 7.0 mg/dL in males and 6.0 mg/dL in females. The data were analyzed using SPSS version 24, with a p-value of ≤ 0.05 considered statistically significant. Results: Of the 237 participants, 127 (53.6%) were males and 110 (46.4%) females, with a mean age of 51 ± 9.02 years. Hyperuricemia was observed in 131 patients (55.3%). The condition was more prevalent in females than in males (p < 0.05). A significant association was noted between hyperuricemia and the duration of diabetic kidney disease. Conclusion: Hyperuricemia is highly prevalent among diabetic kidney disease patients, affecting over half of the studied population. These findings underscore the need for routine screening and early intervention to potentially slow disease progression and reduce related complications.